2017
DOI: 10.1027/0227-5910/a000466
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Prevention of Suicide in Nursing Homes

Abstract: This study confirms the need to continue training on suicide prevention in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This study suggested that residential transitions may be an important point of engagement before the suicide crisis and that more can be done to support the mental health of older adults living in these settings [22]. Couillet et al demonstrated that barriers to preventing suicide in nursing homes lie in caregivers' suicide representation, seen as an expression of residents' autonomy, a response to the suffering associated with aging and the living conditions imposed on older adults in our society [23].…”
Section: Discussionmentioning
confidence: 91%
“…This study suggested that residential transitions may be an important point of engagement before the suicide crisis and that more can be done to support the mental health of older adults living in these settings [22]. Couillet et al demonstrated that barriers to preventing suicide in nursing homes lie in caregivers' suicide representation, seen as an expression of residents' autonomy, a response to the suffering associated with aging and the living conditions imposed on older adults in our society [23].…”
Section: Discussionmentioning
confidence: 91%
“…The view of nursing homes as a place where people with dementia are left to die is broadly shared, even by nursing home staff. 42 Another reason may be a lack of research culture and funding in nursing homes. Other reasons are linked to methodological difficulties, such as high attrition rates expected in older people, which add to the more general difficulties of evaluating suicide prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a total of nine core articles published in the preceding decade and one Older Adult Suicide Prevention Plan. [2,4,[6][7][8][9][10][11][12][13] Statements were extracted and compared against the Task Force for the European Evidence-Based Suicide Prevention Program (EESPP) consensus declaration. [14] Statements were clustered into four operating levels: (1) guiding principles; (2) universal prevention, focused on the entire population as the target-prevention through reducing risk and enhancing health; (3) indicated prevention, symptomatic and 'marked' high-risk individualinterventions to prevent acute disorders or adverse outcomes; and (4) selective prevention for high-risk groups, often focusing on clinical interventions in clinical populations-prevention through reducing risks.…”
Section: Statement Selectionmentioning
confidence: 99%